A modified thermal treatment method for the up-scalable synthesis of size-controlled nanocrystalline titania - Keiteb, Aysar Sabah; Saion, Elias; Zakaria, Azmi; Soltani, Nayereh; Abdullahi, Nura (MDPI, 2016)
Considering the increasing demand for titania nanoparticles with controlled quality for various applications, the present work reports the up-scalable synthesis of size-controlled titanium dioxide nanocrystals with a simple and convenient thermal treatment route. Titanium dioxide nanocrystals with tetragonal structure were synthesized directly from an aqueous solution containing titanium (IV) isopropoxide as the main reactant, polyvinyl pyrrolidone (PVP) as the capping agent, and deionized water as a solvent. With the elimination of the drying process in a thermal treatment method, an attempt was made to decrease the synthesis time. The mixture directly underwent calcination to form titanium dioxide (TiO2) nanocrystalline powder, which was confirmed by FT-IR, energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) analysis. The control over the size and optical properties of nanocrystals was achieved via variation in calcination temperatures. The obtained average sizes from XRD spectra and transmission electron microscopy (TEM) images showed exponential variation with increasing calcination temperature. The optical properties showed a decrease in the band gap energy with increasing calcination temperature due to the enlargement of the nanoparticle size. These results prove that direct calcination of reactant solution is a convenient thermal treatment route for the potential large-scale production of size-controlled Titania nanoparticles.